2022
DOI: 10.3389/fmars.2022.867068
|View full text |Cite
|
Sign up to set email alerts
|

Who Is in Handicrafts: Tooth Morphology and Age Determination as Tools to Assess Vulnerable Dolphins Sotalia spp. Supplying the Trade of Artisanal Charms in Brazil

Abstract: In Brazil, dolphins’ body parts are commonly used as traditional amulets, named as love-charms, while dolphins’ teeth are commercialized in handcrafted necklaces and bracelets. Recent studies on forensic genetics confirmed the Guiana dolphin, Sotalia guianensis, as the principal target of the love-charms trading, with specimens incidentally captured in gillnets suggested as the primary source. As additional support for these investigations, we characterized tooth morphotypes and ages of dolphins used in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…previously for other species of dolphins, such as Cephalorhynchus hectori and Delphinus delphis (Mannocci et al, 2012;Slooten & Lad, 1991). For Guiana dolphins, the effect of bycatch on young mature individuals has been reported in North-Eastern and South-Eastern coastal regions of Brazil (Di Beneditto & Ramos, 2004;Meirelles et al, 2010;Santos et al, 2003) and suggested by Ruenes et al (2022) for the Northern region.…”
Section: Seasonalitymentioning
confidence: 80%
See 1 more Smart Citation
“…previously for other species of dolphins, such as Cephalorhynchus hectori and Delphinus delphis (Mannocci et al, 2012;Slooten & Lad, 1991). For Guiana dolphins, the effect of bycatch on young mature individuals has been reported in North-Eastern and South-Eastern coastal regions of Brazil (Di Beneditto & Ramos, 2004;Meirelles et al, 2010;Santos et al, 2003) and suggested by Ruenes et al (2022) for the Northern region.…”
Section: Seasonalitymentioning
confidence: 80%
“…This practice may account for the high number of stranded dolphins observed in the estuary over the years. Additionally, there is evidence of local populations using dolphin carcasses as bait and for the traditional trade of anatomical parts such as teeth, eyes and skin as magical‐religious amulets (Gravena et al, 2008; Ruenes et al, 2022; Siciliano et al, 2018). This highlights the significant anthropic pressure on this Guiana dolphin MU.…”
Section: Discussionmentioning
confidence: 99%